A late spring in Europe and the adaptability of plants: Epigenetic regulation seems to play a major role in plants' ability to adapt to and remember unusual climate patterns. (13th August 2013) - Hunter, Philip
Abstract : Plants seem to cope with unexpected climate conditions and retain a memory of past climates by epigenetic reprogramming. A better understanding of these mechanisms could allow breeders to create new crop varieties adapted to harsher conditions.